Correction of students negative states by health fitness means as a scientific problem - Vasyl Khlopetskyi; Serhii Kuryliuk (Kazimierz Wielki University, 2017)
The purpose of the study is to carry out a theoretical and methodological analysis of scientific data on the occurrence and correction problem of student's negative mental states. The study of occurrence and correction peculiarities of negative mental states is especially important during the study of students in higher education institutions, as this period is characterized by an intensive personality development, formation of its intellectual, emotional, volitional, motivational spheres, value orientations, professionalization and self-determination. The dominance of these states has a destructive effect on students' lives, the processes of their personal development and self-realization. Scientists and practitioners emphasize that the task of fitness is to improve health, vitality, increase general and special performance, physical qualities education, body defects formation and correction, psychoprophylaxis, psychocorrection, psychoregulation, vital energy gaining, liveliness, cheerful mood, stress resistance. Health fitness is a highly effective and accessible physical activity form for everyone. As a HLS forming means of school and student youth, the priorities of health fitness aimed at improving health are exercise using to improve physical body condition, posture correction, psychological regulation and self-regulation, balanced diet and bad habits abandonment. Prospects for further research are to study the effectiveness of the author's health fitness technologies for correction of mental students' states.